F.l.t.r. Avocat André Klotz, Jeanne Humbert, Eugène Humbert, Marianne Labarthe. Procès de Jeanne Humbert. Text on back
F.l.t.r. Avocat André Klotz, Jeanne Humbert, Eugène Humbert, Marianne Labarthe. Procès de Jeanne Humbert. Text on back.